Process Oriented Guided Inquiry Learning (POGIL): Its Effectiveness in Increasing Students' Scientific Literacy Skills in Plant Physiology Course - Yennita; Astriawati, Fitri; Jumiarni , Dewi (BIOEDUSCIENCE, 2024)
Background: Today, the main goal of science learning is to create a scientifically literate society by understanding mathematics, physics, chemistry, biology, and technology. Therefore, this research aims to determine the effectiveness of the process-oriented guided inquiry learning (POGIL) model in improving students' scientific literacy skills in a Plant Physiology course. Methods: This study was a quasi-experiment using a control group pre-test and post-test design with 32 students as research subjects. Data collection techniques used tests and research data were analyzed using a one-way ANCOVA statistical test. Results: The results showed a significant difference in scientific literacy skills between the control and experimental classes by controlling for students' initial scientific literacy [F(1,61) = 1977.228, p < 0.001], effect size np2 = 0.97. Conclusions: Therefore, the POGIL model is highly effective in increasing students' scientific literacy skills in the Plant Physiology Course.